2006
DOI: 10.1074/jbc.m502000200
|View full text |Cite
|
Sign up to set email alerts
|

Occupancy of a Single Anesthetic Binding Pocket Is Sufficient to Enhance Glycine Receptor Function

Abstract: Alcohols and volatile anesthetics enhance the function of inhibitory glycine receptors (GlyRs). This is hypothesized to occur by their binding to a pocket formed between the transmembrane domains of individual ␣1 GlyR subunits. Because GlyRs are pentameric, it follows that each GlyR contains up to five alcohol/anesthetic binding sites, with one in each subunit. We asked how many subunits per pentamer need be bound by drug in order to enhance receptormediated currents. A cysteine mutation was introduced at amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…This propofol was optimized into position using molecular mechanics with the CHARMm force field, followed by molecular dynamics, 26 while allowing for sidechain flexibility with only backbone atoms fixed. While the work of Mihic et al has demonstrated that occupancy of only one binding site is sufficient to enhance the homologous glycine receptor’s function, 27 the work of Forman et al . 2831 shows that propofol’s enhancing action in GABAaR requires occupancy of perhaps three propofol sites.…”
Section: Methodsmentioning
confidence: 99%
“…This propofol was optimized into position using molecular mechanics with the CHARMm force field, followed by molecular dynamics, 26 while allowing for sidechain flexibility with only backbone atoms fixed. While the work of Mihic et al has demonstrated that occupancy of only one binding site is sufficient to enhance the homologous glycine receptor’s function, 27 the work of Forman et al . 2831 shows that propofol’s enhancing action in GABAaR requires occupancy of perhaps three propofol sites.…”
Section: Methodsmentioning
confidence: 99%
“…From mutagenesis and physiologic studies, it is believed that the binding site for volatile anesthetics on GlyR consists of amino acids located in TM2 and TM3 that form an intrasubunit cavity (Mihic et al, 1997;Roberts et al, 2006;Duret et al, 2011) and include residues S267 (TM2) and A288 (TM3) (Horani et al, 2015) (Fig. 2A,D).…”
Section: Molecular Sites For the Functional Regulation Of Glyrmentioning
confidence: 99%
“…In addition, ethanol, in the absence of agonist, causes a conformational change in the receptor that can change accessibility of TM residues (Jung et al , 2005;Jung and Harris, 2006). Finally, PMTS occupancy of a single anesthetic binding pocket within the GlyR pentamer is sufficient to enhance receptor function (Roberts et al , 2005). Taken together, these studies support the notion that TM position 267 is capable of initiating the actions of ethanol.…”
Section: Region-specific Targets and Mechanisms Of Ethanol Actionmentioning
confidence: 99%